Metal–organic-framework derived Co–Pd bond is preferred over Fe–Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol. Issue 24 (24th May 2019) - Pendem, Saikiran; Bolla, Srinivasa Rao; Morgan, David J.; Shinde, Digambar B.; Lai, Zhiping; Nakka, Lingaiah; Mondal, John
Abstract : The metal–organic-framework-derived Co–Pd bond can more efficiently catalyze the reductive upgrading of furfural to tetrahydrofurfuryl alcohol production as compared to the Fe–Pd bond. Abstract : Combined noble-transition metal catalysts have been used to produce a wide range of important non-petroleum-based chemicals from biomass-derived furfural (as a platform molecule) and have garnered colossal research interest due to the urgent demand for sustainable and clean fuels. Herein, we report the palladium-modified metal–organic-framework (MOF) assisted preparation of PdCo3 O4 and PdFe3 O4 nanoparticles encapsulated in a graphitic N-doped carbon (NC) matrix via facile in situ thermolysis. This provides a change in selectivity with superior catalytic activity for the reductive upgrading of biomass-derived furfural (FA). Under the optimized reaction conditions, the newly designed PdCo3 O4 @NC catalyst exhibited highly efficient catalytic performance in the hydrogenation of furfural, providing 100% furfural conversion with 95% yield of tetrahydrofurfuryl alcohol (THFAL). In contrast, the as-synthesized Pd–Fe3 O4 @NC afforded a THFAL yield of 70% after an 8 h reaction with four consecutive recycling tests. Based on different characterization data (XPS, H2 -TPR) for nanohybrids, we can conclude that the presence of PdCo-N x active sites, and the multiple synergistic effects between Co3 O4 and Pd(ii ), Co3 O4 and Pd 0, as well as the presence of N in the carbonaceous matrix, are responsible for the superior catalytic activity and improved catalyst stability. Our strategy provides a facile design and synthesis process for a noble-transition metal alloy as a superior biomass refining, robust catalyst via noble metal modified MOFs as precursors.